Failing Better: Understanding and Supporting Students Through Failure in Higher Education - Gallina, Melissa; Maclachlan, John; Kandiah, Akalya (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This study explores how failure is understood within higher education through the perspectives of university administrators at a mid-sized research-intensive institution in Ontario. Using in-depth interviews, the study reveals that failure in higher education exists at the intersection of individual student experiences, institutional structures, and pedagogical approaches. Themes in the discourse surrounding student failure include the fear of failing for the first time, a lack of preparedness for university study, the impacts of imposter syndrome, challenges in taking ownership of academic journeys, unique barriers faced by non-traditional students, and institutional barriers that reinforce failure. While failure is promoted as a learning opportunity in higher education, institutional structures and practices often contradict this view with punitive measures that can impact students' academic careers. Building on Carr's Pedagogy of Failure, this research emphasizes the need for approaches that prioritize emotional well-being, open dialogue, and structured support through failure. One recommendation is to use co-curricular activities, such as living learning communities, as safe spaces for students to experiment with and learn from failure without academic consequences. Overall, institutions need to support student learning through failure better while also addressing systemic barriers and providing equitable support for diverse student populations.